Spheroid Size Does not Impact Metabolism of the β-blocker Propranolol in 3D Intestinal Fish Model - Langan, Laura M.; Owen, Stewart F.; Trznadel, Maciej; Dodd, Nicholas J. F.; Jackson, Simon K.; Purcell, Wendy M.; Jha, Awadhesh N. (Frontiers in Pharmacology, 2018)
Compared to two-dimensional (2D) cell culture, cellular aggregates or spheroids (3D) offer a more appropriate alternative in vitro system where individual cell-cell communication and micro-environment more closely represent the in vivo organ; yet we understand little of the physiological conditions at this scale. The relationship between spheroid size and oxygen microenvironment, an important factor influencing the metabolic capacity of cells, was first established using the fish intestine derived RTgutGC cell line. Subsequently, pharmaceutical metabolism (Propranolol), as determined by high performance liquid chromatography, in this intestinal model was examined as a function of spheroid size. Co-efficient of variation between spheroid size was below 12 % using the gyratory platform method, with the least variation observed in the highest cell seeding density. The viable, high oxygen micro-environment of the outer rim of the spheroid, as determined by electron paramagnetic resonance (EPR) oximetry, decreased over time, and the hypoxic zone increased as a function of spheroid size. Despite a trend of higher metabolism in smaller spheroids, the formation of micro-environments (quiescent, hypoxic or anoxic) did not significantly affect metabolism or function of an environmentally relevant pharmaceutical in this spheroid model.